Penanganan dan Pencegahan Bullying di Sekolah - Mokh. Thoif; Sulistyani Eka Lestari; Nur Aziz; Muhari Muhari; Nuris Pratama Wisesa; Didik Wahyu Sugianto; Sujono Ali Mujahidin (Lembaga Pengembangan Kinerja Dosen, 2025)
Preventing and addressing bullying in schools is crucial for creating a safe and supportive educational environment for student development. Bullying, whether physical, verbal, or psychological, can have long-term impacts on the mental and emotional well-being of students who are victims. This study aims to explore strategies implemented by schools to address and prevent bullying, and to analyze the challenges faced in implementing these strategies. The research employed a descriptive qualitative approach with a case study approach in several schools in Indonesia. Data were collected through in-depth interviews with principals, teachers, students, and parents, as well as observations of school programs. Document analysis of school policies on bullying was also conducted. The study found that although most schools have policies related to bullying, insufficient supervision and a lack of parental involvement in supporting these policies remain obstacles. Other factors influencing the effectiveness of bullying prevention are teacher awareness and skills in addressing students' social issues. This study recommends a community-based approach, in which all parties, from students, teachers, and parents, play an active role in creating an anti-bullying culture. Training programs for teachers and outreach to students regarding the negative impacts of bullying need to be improved. With stronger policies and increased awareness, it is hoped that bullying can be minimized and addressed, making schools a safe place for learning and development. Implementing this community-based approach is expected to create a culture that is free from bullying and provide better support for victims of bullying.